Operation planning for heat pump in a residential building - Shota KIMATA; Takayuki SHIINA; Tetsuya SATO; Ken-ichi TOKORO (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2020)
In an effort to tackle environmental problems, sustainable policies that have a low environmental impact on the local community are being implemented in many countries, including Japan. One approach is the smart community, which is a policy to evaluate the cost of the entire community, considering each interaction while dividing society into seven fields: power, gas, water, railway, industry, business, and home models. In this study, we evaluate and optimize the home model. We develop an optimization model for the operation plan of energy storage equipment in a residential building as part of a smart community. The purpose of this model is to improve electricity costs from the demand profile and provide stable power supply from the supply profile. Therefore, this model controls the operation of energy storage equipment and also performs load leveling. It is intended to reduce the total power consumption during peak hours by operating the energy storage equipment at night, when the usage of other electrical appliances is low. A stochastic programming model is formulated using scenarios that represent the uncertainty of power and heat demand. This formulation assumes continuous operation in a residential building. We demonstrate the usefulness of the stochastic programming model by comparing it with the deterministic model. As an economic assessment, we compare the daily beneficial expense of the existing model with our new model of daily operations by following the improvement factors. Our model not only lowers peak total power consumption but also achieves load leveling. The total operating time of energy storage equipment is also reduced.